Optimization of subcritical water extraction for pectin extraction from cocoa pod husks using the response surface methodology - Anoraga, Satria Bhirawa; Shamsudin, Rosnah; Hamzah, Muhammad Hazwan; Sharif, Suzannah; Saputro, Arifin Dwi; Mohd Basri, Mohd Salahuddin (Elsevier, 2024)
This study optimized subcritical water extraction (SWE) conditions to maximize pectin yield from cocoa pod husk (CPH) and compared the characteristics of CPH pectin extracted through SWE with those of CPH pectin obtained through conventional extraction (CE) with citric acid. The Box–Behnken experimental design was employed to optimize SWE and examine the influence of process parameters, including temperature (100 °C–120 °C), extraction time (10–30 min), and solid:liquid ratio (SLR) (1:30–2:30 g/mL), on pectin yield. The maximum pectin yield of 6.58% was obtained under the optimal extraction conditions of 120 °C for 10 min with 1:15 g/mL SLR and closely corresponded with the predicted value of 7.29%. Compared with CE, SWE generated a higher yield and resulted in a higher degree of esterification, methoxyl content, and anhydrouronic acid value but a lower equivalent weight. The extracted pectin was pure, had low-methoxyl content, and similar melting and degradation temperatures.